Effects of Different Attack Angles and Guide Vane Numbers on the Vortex-solid Interaction Noise of Axial Flow Fan - Z. Tu; Y. Li; J. Zhou; Z. Chen (Journal of Applied Fluid Mechanics)
This paper utilizes experiments and numerical simulations to investigate the effects of different attack angles of the rotor and the number of guide vanes on the vortex-solid interaction and noise generation of an axial flow fan. The noise and the flow field are measured using far-/near-field microphone arrays and the particle imaging velocimetry (PIV) technique, respectively, conducted in a fully anechoic wind tunnel measuring 0.5m × 0.4m. The numerical simulation uses Large Eddy Simulation (LES). The results reveal that the axial flow fan's noise is all influenced by vortex-solid interaction in various degrees. The angle of attack α changes the noise magnitude by affecting the blades' interaction with the surrounding fluid, causing different pressure pulsations. As the angle of attack α of the rotor blade increases, the tonal noise at the harmonics increases significantly. The increase in noise is partly related to the increment of flow separation caused by the attack angle and partly related to the periodic movement of the rotor blade wake vortex from the front of the static blade to the middle and rear of the static blade. The irregularly distributed static blades reduce the appearance of tonal noise while slightly increasing the work capacity.